Spatial distribution of carbonaceous aerosol in the southeastern United States using molecular markers and carbon isotope data - M* Zheng; Ke L; ES Edgerton; J.J. Schauer; MY Dong; AG Russell (J. Geophys. Res., 2006)
Spatial variations of source contributions to fine organic carbon (OC) and fine particles in the southeastern United States were investigated using molecular marker-based chemical mass balance modeling (CMB-MM) and carbon isotope analysis. Nine primary emission sources were resolved with wood combustion (average 1.73 μg m−3, 23 ± 14% of measured OC) being the most dominant contributor to OC, followed by gasoline engine exhaust (0.45 μg m−3, 6.1 ± 6.2% of OC), diesel engine exhaust (0.43 μg m−3, 4.8 ± 4.1% of OC), and meat cooking (0.30 μg m−3, 4.1 ± 2.6% of OC). Measurable contributions from vegetative detritus, cigarette smoke, road dust, and natural gas exhaust were found. The impact of coke facilities was estimated for the first time in Birmingham, Alabama, and contributed 0.52 μg m−3 on average to fine OC. The unexplained OC accounted for 54 ± 26% of measured OC, possibly because of contributions from secondary OC, other unidentified primary sources and the possible positive artifact of OC. The urban excess of OC from diesel exhaust, gasoline exhaust and meat cooking can be seen from the results of the urban-rural pair in Alabama. Detailed chemical analysis revealed the wood burning episode at the rural site and an episode of secondary formation in the study region. The 14C analysis, a tool to study the relative contributions of contemporary and fossil carbon contents of fine particles, agreed well with the CMB-MM analysis. Both reflected a higher fossil fraction of carbon at urban sites especially in Birmingham, Alabama.